2006
DOI: 10.1243/09544054jem537
|View full text |Cite
|
Sign up to set email alerts
|

Investigating mechanical anisotropy and end-of-vector effect in laser-sintered nylon parts

Abstract: DOI: 10.1243/09544054JEM537Abstract: A study investigating the effects of part-build orientation in the laser sintering process is presented. The investigation uses tensile, flexural, and compression testing methods to assess the changes in the mechanical properties of laser-sintered nylon-12 parts. The test parts were built in the x, y, and z orientations with the x axis parallel to the direction of the laser scanning, the y axis perpendicular to the direction laser of scanning, and the z axis in the directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
91
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 14 publications
15
91
0
Order By: Relevance
“…b a b a This would help to explain the existence of a maximum achievable thermal penetration depth within the process. This can also be related to SLS research 18 which shows that sintering occurs to a lesser degree in the z direction than in the x and y directions, indicating that less thermal energy is transferred in the z direction.…”
Section: Discussion Of Sintering Characteristicsmentioning
confidence: 59%
“…b a b a This would help to explain the existence of a maximum achievable thermal penetration depth within the process. This can also be related to SLS research 18 which shows that sintering occurs to a lesser degree in the z direction than in the x and y directions, indicating that less thermal energy is transferred in the z direction.…”
Section: Discussion Of Sintering Characteristicsmentioning
confidence: 59%
“…Nylon, a wellresearched and optimised polymeric material for laser sintering showed a difference of 16% in tensile strength in the X, Y and Z axes. [28] Previous study on laser sintered HP3 PEK showed a significantly higher difference in tensile strength amongst the three directions [29] (approx. 50%), which could the result of the higher processing temperatures and therefore higher thermal gradients between layers in Z axis.…”
Section: Ls-pekmentioning
confidence: 92%
“…They also introduced the terminology of "degree of particle melt (DPM)" when discussing the layering effect similar to the one noticed here. Ajoku et al, [28] explained clearly the bonding mechanisms and temperature differences that take place between vectors and layers and led to the layered structure. The neck growth is significantly smaller in Z direction than X and Y axes.…”
Section: Ls-pekmentioning
confidence: 99%
“…The manufacturing process builds up parts layer by layer, so the bonding between layers, warping/curling effects which come into play and the interaction between layers impact heavily on the resulting mechanical strength. A variety of studies have been performed investigating the anisotropy of SLS parts, where [18] took standard process parameters and built tensile bars in the x,y and z orientations. The samples were subjected to flexural and compressive tests to determine the degree of anisotropy [19] printed nylon PA12 tensile bars again across the x,y and z directions, but this time using both new and aged powder.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%